Estudos de indicadores de sustentabilidade e sua correlação com a geração de resíduos sólidos urbanos na Cidade de Fortaleza-CE - Carvalho Júnior, Francisco Humberto de (2013)
The rate of generation of municipal solid waste (MSW) has increased much more than the urban population, even in regions where the birth rate is high. The reasons for this growth can be various, yet the cultural and economic factors are the most relevant. The environmental impacts of this growth can be noticed especially in large cities such as Fortaleza, CE, with characteristics of commercial and tourist city. This research sought to examine the reasons for the growth of the urban waste, particularly in Brazil and in the city of Fortaleza. It was sought as the main hypothesis the correlation of MSW generation and the economic growth, caused by consumerism. We studied the influential sustainability indicators for the growth of waste generation. Through the SPSS statistical tool, we selected the related indicators, and then we applied a multiple regression to find the response equation that quantifies the total of waste to Fortaleza, in the period between 2001 and 2011. The results obtained represent the indicators well because the reliability was 80.9% of the predicted value. The remaining 19.1% is explained by other indicators that are not in the model. Sustainability indicators chosen were: INPC, IPCA, GINI Indicator, power consumption, GDP, consumption of treated water, time, HDI and the urban population. Among all the indicators analyzed, those ones that showed the highest correlation to the response equation were, in order, the electricity consumption, GDP, consumption of treated water, time, HDI and the urban population. According to the equation-response, validated for the city of Fortaleza, allowed to conclude on the need to involve the model of production and consumption with the modern generation of municipal solid waste.